Capital Controls and Implications for Surveillance and coordination: Brazil and Latin America - Márcio Gomes Pinto Garcia (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2015)
Brazil has been one of the most active country in intervening in FX markets though several forms: sterilized interventions and foreign reserves accumulation, controls on capital inflows and FX interventions through domestic derivatives markets. During the golden phase of the commodity super-boom generated by China, the goal of the FX interventions was to deter real exchange rate appreciation. With the Brazilian experience in mind, we extract lessons for surveillance and coordination. We argue that capital controls were not a very useful tool to deter real exchange rate appreciation. Comparing Brazil with Chile, the poster child of capital controls in the nineties that decided not to use them again during the commodity super-boom of this century, we conclude that an adequate fiscal policy stance could provide much better results than the use of capital controls. Furthermore, we claim that the use of capital controls in Brazil helped to avoid necessary changes in the fiscal policy stance. Analyzing the recent experiences of Colombia and Peru also do not bring much support to capital controls. Therefore, when analyzing the implications for surveillance and coordination, international institutions, as the IMF, should take into consideration that, no matter how many caveats are listed before its guidelines, capital controls may serve mainly to bypass needed changes in macroeconomic policy, thereby jeopardizing better economic performance.
Keywords: 330